The scientific life of merchants through a book in order to order in the history of Aleppo by Ibn Al-Adim (d.660 AH - 1261 AD) - Sabaa, Alaa Oraibi; Majeed, Ali Naif (Al-Adab Journal, 2015)
Longer in order to demand in the history of Aleppo important sources in the study of history and biographies of the men , and given his historian of stature and scientific as well as the book , we will try to identify the subject of scientists traders through this book and the title of our topic : ( scientists traders through in order to demand Date of Alepp) The son of incompetent in his scholars traders did not remind them of historical sources other , and this is the work of important topics where historians and scientists who did not remind them other than by highlighting the scientists were working in the trade ’ and that their work did not stop them from continuing their knowledge and dissemination of science , but Conversely work in the trade helped them a lot in this area , through the movement of the country has takers of the elders of that country , as well as transferred their science that they own Vognohm knowingly diverse , and it was these scientists had been transferred this science to their home countries by Halqathm scientific which they rate them on their students who been mentioned born each dealer with their elders , and then search section to two sections , taking the first section life son incompetent in terms of his name , and his nickname , and accounted for , and the proportion and origin , and his birth and upbringing , and his marriage and family formation , and the qualities and morals , and his trips in the application of science , and its effects and writings , and its sciences and knowledge , and the realization , and death . The second topic addressed the translation of scientists traders who have been mentioned in the book in order to demand in the history of Aleppo to the son of smokeless were their sequence by alphabets , asset God Almighty that benefit us in this work and that makes it